Circular RNA Foxo3 in cardiac ischemia‐reperfusion injury in heart transplantation: A new regulator and target. Issue 9 (2nd February 2021) - Su, Yale; Zhu, Cuilin; Wang, Bowen; Zheng, Hao; McAlister, Vivian; Lacefield, James C.; Quan, Douglas; Mele, Tina; Greasley, Adam; Liu, Kexiang; Zheng, Xiufen
Abstract : Ischemia‐reperfusion (I/R) injury occurring in heart transplantation (HT) remains as a leading cause of transplant heart graft failure. Circular RNAs (circRNAs) play important roles in gene regulation and diseases. However, the impact of circRNAs on I/R injury during HT remains unknown. This study aims to investigate the role of circular RNA Foxo3 (circFoxo3) in I/R injury in HT. Using an in vivo mouse HT model and an in vitro cardiomyocyte culture model, we demonstrated that circFoxo3 is significantly upregulated in I/R‐injured hearts and hypoxia/reoxygenation (H/R)‐damaged cardiomyocytes. Knockdown of circFoxo3 using siRNA not only reduces cell apoptosis and death, mitochondrial damage, and expression of apoptosis/death‐related genes in vitro, but also protects heart grafts from prolonged cold I/R injury in HT. We also show that circFoxo3 interacts with Foxo3 proteins and inhibits the phosphorylation of Foxo3 and that it indirectly affects the expression of miR‐433 and miR‐136. In conclusion, circRNA is involved in I/R injury in HT and knockdown of circFoxo3 with siRNA can reduce I/R injury and improve heart graft function through interaction with Foxo3. This study highlights that circRNA is a new type of molecular regulator and a potential target for preventing I/R injury in HT. Abstract : Knockdown of circular RNA Foxo3 reduces cell apoptosis and ischemia reperfusion injury, as well as preserving heart graft function, highlighting that circular RNA may be a novel therapeutic target for preventing cardiac injury. Videos available in the online supporting information.